Construction of self-supported hierarchical CuCo2O4 dendrites as faradaic electrode material for redox-based supercapacitor applications. (20th November 2022) - George, Amala; Kundu, Manab
Abstract: The hierarchical CuCo2 O4 dendrites electrode was directly constructed by a rapid and facile electrochemical route followed by thermal treatment. The engineered dendrites illustrate vertically aligned architecture with primary midrib connected with ceaseless secondary trunks subdivided to tertiary trunks in an ordered arrangement. CuCo2 O4 exhibited superior capacitive property (938.4 C g −1 ), compared to the corresponding mono metal oxides (CuO = 341.6 and Co3 O4 = 65.04 C g −1 ) at applied current density of 12 A g −1 . Owing to the constructive features of uninterrupted conductive pathways, multivalent redox species, and structural advantages of CuCo2 O4 dendrites, the rationally developed faradaic electrode offers improved capacity of 597.12 C g −1 for 5000 cycles with retention of 83.5% at higher current density value of 30 A g −1 . A faradaic supercapacitor was fabricated with CuCo2 O4 and activated carbon as cathode and anode, delivered capacity value of 223.65 C g −1 at 8 A g −1 with 93.91% retention value upto 5000 cycles at current density of 30 A g −1 . The assembled device exhibited a high energy density of 87.465 W h kg −1 at 4.9 kW kg −1 and still maintained to deliver 30.741 W h kg −1 at 50.99 kW kg −1 upon high applied current density of 30 A g −1 . Thus these perspectives pronounce the binder free, fast and scalable synthetic route for the preparation of hierarchical nanostructures for high performance energy storage devices also provides a platform for improvising energy crisis and storage demands.